Wildlife sequences of islet amyloid polypeptide (IAPP) identify critical species variants for fibrillization. (September 2015) - Fortin, Jessica S.; Benoit-Biancamano, Marie-Odile
Abstract Amyloid can be detected in the islets of Langerhans in a majority of type 2 diabetic patients. These deposits have been associated with β-cell death, thereby furthering diabetes progression. Islet amyloid polypeptide (IAPP) amyloidogenicity is quite variable among animal species, and studying this variability could further our understanding of the mechanisms involved in the aggregation process. Thus, the general aim of this study was to identify IAPP isoforms in different animal species and characterize their propensity to form fibrillar aggregates. A library of 23 peptides (fragment 8–32) was designed to study the amyloid formation using in silico analysis and in vitro assays. Amyloid formation was impeded when the NFLVH motif found in segment 8–20 was substituted by DFLGR or KFLIR segments. A 29P, 14K and 18R substitution were often present in non-amyloidogenic sequences. Non-amyloidogenic sequences were obtained from Leontopithecus rosalia, Tursiops truncatus and Vicugna pacos. Fragment peptides from 34 species were amyloidogenic. To conclude, this project advances our knowledge on the comparative pathogenesis of amyloidosis in type II diabetes. It is conceivable that the additional information gained may help point towards new therapeutic strategies for diabetes patients.